КРИТЕРІЇ ОЦІНЮВАННЯ ЯКОСТІ ЕЛЕКТРОЕНЕРГІЇ, ЩО ВИРОБЛЯЄТЬСЯ ОБ’ЄКТАМИ РОЗОСЕРЕДЖЕНОЇ ГЕНЕРАЦІЇ - Жаркін, А.Ф.; Палачов, С.О. (Інститут електродинаміки НАН України, Київ, 2018)
The disadvantages of the criterion used in Ukraine for estimating the quality of electricity produced by the objects of dispersed generation is analyzed. Based on the analysis of international experience, additional criteria have been proposed that uses the maximum level of emission of disturbances from equipment and can be provided at the stage of its production. The use of this criterion will facilitate the wider using in Ukraine of renewable energy sources of various capacities by simplifying the connection procedure, while maintaining the proper power quality.  References 2.